Treatment of a Chronic Elbow Dislocation With an Internal Fixator. (August 2021) - Schultz, Blake J.; Lowe, Dylan T.; Pean, Christian A.; Egol, Kenneth A.
Abstract : Summary: There are a variety of ways to treat chronic elbow dislocations, including repeat closed reduction and immobilization, transarticular pinning, temporary bridge plating, hinged or rigid external fixation, and internal fixator application. Although each have distinct advantages and disadvantages, avoiding recurrent instability is critical. The internal-fixator is a relatively new option to maintain a stable, concentric reduction and facilitate early range of motion. This article and accompanying video describe the surgical technique of using an internal joint stabilizer for treatment of a chronically unstable ulnohumeral joint.